Capture and Governance at Local and National Levels - Bardhan, Pranab; Mookherjee, Dilip (American Economic Review, 2000)
135 Despite the importance of this issue, not much systematic research appears to have been devoted to assessing the relative susceptibility of national and local governments to interestgroup capture. Here we describe a model of two-party electoral competition with “probabilistic” voting behavior and lobbying by specialinterest groups based on David Baron (1994) and Gene Grossman and Elhanan Helpman (1996) that helps identify determinants of relative capture at different levels of government. These include relative levels of voter awareness and interest-group cohesiveness, electoral uncertainty, electoral competition, heterogeneity of districts with respect to inequality, and the electoral system. While some of these uphold the traditional Madisonian presumption, others are likely to create a tendency for lower capture at the local level, so the net effect is theoretically ambiguous. This suggests that the extent of relative capture may be context-specific and needs to be assessed empirically.